TGF-β1 is involved in senescence-related pathways in glomerular endothelial cells via p16 translocation and p21 induction - Sayo Ueda (Nature Portfolio, 2021)
Abstract p16 inhibits cyclin-dependent kinases and regulates senescence-mediated arrest as well as p21. Nuclear p16 promotes G1 cell cycle arrest and cellular senescence. In various glomerular diseases, nuclear p16 expression is associated with disease progression. Therefore, the location of p16 is important. However, the mechanism of p16 trafficking between the nucleus and cytoplasm is yet to be fully investigated. TGF-β1, a major cytokine involved in the development of kidney diseases, can upregulate p21 expression. However, the relationship between TGF-β1 and p16 is poorly understood. Here, we report the role of podocyte TGF-β1 in regulating the p16 behavior in glomerular endothelial cells. We analyzed podocyte-specific TGF-β1 overexpression mice. Although p16 was found in the nuclei of glomerular endothelial cells and led to endothelial cellular senescence, the expression of p16 did not increase in glomeruli. In cultured endothelial cells, TGF-β1 induced nuclear translocation of p16 without increasing its expression. Among human glomerular diseases, p16 was detected in the nuclei of glomerular endothelial cells. In summary, we demonstrated the novel role of podocyte TGF-β1 in managing p16 behavior and cellular senescence in glomeruli, which has clinical relevance for the progression of human glomerular diseases.